Low levels of plasma protein S, protein C and coagulation factor XII during early pregnancy and adverse pregnancy outcome - Ebina, Yasuhiko; Ieko, Masahiro; Naito, Sumiyoshi; Kobashi, Gen; Deguchi, Masashi; Minakami, Hisanori; Atsumi, Tatsuya; Yamada, Hideto (Thrombosis and Haemostasis, 2015)
It was the study objective to evaluate whether low levels of plasma protein S (PS) activity, free PS, protein C (PC) activity and coagulation factor XII (FXII) during early pregnancy are related to adverse pregnancy outcomes. Peripheral blood samples were obtained at 8–14 gestational weeks (GW) from a consecutive series of 1,220 women. The levels of plasma PS activity, free PS, PC activity, and FXII were measured. Cut-off values were defined as < 1st, < 5th, and < 10th percentiles of values obtained from 933 women whose pregnancies ended in normal deliveries without complications. PS activity of < 10th percentile yielded risks of pregnancy-induced hypertension (PIH) and severe PIH, while free PS level of < 5th percentile yielded a risk of preeclampsia. FXII level of < 1st percentile yielded a risk of premature delivery (PD) at < 34 GW. None was associated with PD at < 37 GW, fetal growth restriction or fetal loss. A multivariate analysis demonstrated that PS activity of < 10th percentile (odds ratio 5.9, 95 % confidence interval 1.7–18.1) and body mass index (BMI) ≥ 25 kg/m2 (4.3, 1.1–13.3) were independent risk factors for severe PIH. Similarly, free PS level of < 5th percentile (4.4, 1.0–14.3) and BMI ≥ 25 kg/m2 (4.0, 1.3–10.9) were independent risk factors for pre-eclampsia. In conclusion, women with low levels of plasma PS activity and free PS during early pregnancy might have increased risks of PIH, severe PIH or pre-eclampsia. Women with low FXII level might have an increased risk of PD at < 34 GW.
Keywords: Factor XII; pregnancy; pregnancy-induced hypertension; premature delivery; protein C; protein S